The Circular Economy of the Islamic Group Lending Model: Lending Money for Garbage in Return - Yaser Taufik Syamlan (Jurnal Internasional Ekonomi Islam, 2020)
The Model of Group Lending has been flourishing in the Microfinance Industry. This model has been used widely in the world to serve the needy and un-bankable group of people by lending money plus interest addition. In Islamic finance also embrace this model by omitting the interest and applying the Qardul Hassan to finance the members so that they can fulfill their daily need. The problem of this divine scheme is the sustainability of the microfinance since they have a burden to bare the operational cost due to the non – interest feature of the financing. This paper tries to solve this problem by utilizing the household garbage as the media to repay the Qardul Hassan financing to the Islamic Microfinance Institution (IMFI) so that it can be processed by the IMFI to create more added value product, selling it to get more income and achieving the organization sustainability.